Avaliação da segurança materno-fetal, da mutagenicidade e do efeito hipoglicemiante de extratos secos obtidos das folhas de Azadirachta indica A. Juss (Meliaceae) - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Azadirachta indica A. Juss. (Meliaceae) is popularly used in Asian countries for the treatment of diseases such as malaria, leprosy, diabetes, ulcers, skin diseases and others.. In addition, the leaves of this species have anti- inflammatory, antifungal, antioxidant, hypoglycemic, antibacterial and antitumor activity. Although A. indica leaves are widely used by the population and have relevant therapeutic properties, the safety of their use in pregnancy needs to be better investigated. Therefore, this study evaluated the maternal- fetal safety, mutagenicity and hypoglycemic effect of dry extracts obtained from the leaves of A. indica in Wistar rats. For this purpose, the production of the ethanolic extract of the leaves of A. indica followed by its spray drying. For characterization of the extract, the content of total flavonoids, expressed as rutin, was determined by spectrophotometric method and rutin was quantified by high performance liquid chromatography. The maternal and fetal toxicity test was performed in female Wistar rats according to the guidelines of protocol 421 of the OECD, the micronucleus test according to protocol OECD 474 and the hypoglycemic effect was evaluated in male Wistar rats. In the evaluation of maternal and fetal toxicity, 40 pregnant Wistar rats (n=10/group) were treated for 21 days with vehicle or dry extract of A. indica leaves at doses of 300, 600 or 1200 mg/kg. Parameters of reproductive performance, water consumption, feed, body mass gain, biochemical parameters, histopathology and organ mass were evaluated.The micronucleus test was performed on cells of the bone media of these rats to verify the incidence of micronucleated immature erythrocytes. To evaluate the hypoglycemic effect, 24 diabetic rats (n=6/group) received: (i) vehicle (inert microcapsules); (ii) microencapsulated extract of A. indica 750 mg/kg; (iii) vehicle (adjuvants); (iv) dry extract of A. indica 750 mg/kg. As for the results, the total flavonoid content of the dry extract, expressed as rutin, ranged from 2.64 to 3.01%. The rutin content of the extract was 1.07%. In the study of reproductive and developmental toxicity, no behavioral and clinical signs of toxicity were observed in females during the gestational period, nor in relation to body mass gain, water consumption and feed, biochemical parameters and reproductive performance between groups. There was no mutagenicity or carcinogenicity in the micronucleus test. The glycemic levels of the animals did not suffer significant reduction during the treatment. Thus, it is concluded that the dry extract of A. indica leaves did not present maternal-fetal toxicity when administered during 21 days of pregnancy and did not present mutagenicity or carcinogenicity. The extract showed no hypoglycemic effect in diabetic rats.
Evaluation of maternal-fetal safety, mutagenicity and hypoglycemic effect of dry extracts obtained from leaves of Azadirachta indica A. Juss (Meliaceae
Keywords: Toxicidade reprodutiva; Azadirachta indica A. Juss. (Meliaceae); Anomalias congênitas; Embriotoxicidade; Fetotoxicidade; Flavonoides totais; Spray drying; Teratogênese; Embryotoxicity; Fetototoxicity.; Total flavonoids; Spray Drying; Teratogenesis; Reproductive toxicity.; OUTROS; CIENCIAS DA SAUDE